1978
DOI: 10.1093/ajcp/70.2.230
|View full text |Cite
|
Sign up to set email alerts
|

Hemagglutination Tests for Syphilis Antibody

Abstract: In a study of serodiagnosis of syphilis, the authors compared the specificities and sensitivities of two hemagglutination tests, a sheep-erythrocyte test (MHA-TP) and a trukey-erythrocyte test (TPHA), with those of the Fluorescent Treponemal Antibody-Absorption (FTA-ABS) test. In tests of sera from 935 patients without syphilis, the MHA-TP, TPHA, and FTA-ABS tests were reactive for 0.96, 0, and 1.3% respectively. The false-positive results were usually transient and not associated with underlying illness. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Of the two standard treponemal test systems (fluorescent antibody and hemagglutination) currently in use, the MHA-TP gives fewer false-positive test results (87,111,210). In general, the occurrence of false-positive hemagglutination tests is rare in ''healthy'' persons (Ͻ1%).…”
Section: Treponemal Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the two standard treponemal test systems (fluorescent antibody and hemagglutination) currently in use, the MHA-TP gives fewer false-positive test results (87,111,210). In general, the occurrence of false-positive hemagglutination tests is rare in ''healthy'' persons (Ͻ1%).…”
Section: Treponemal Testsmentioning
confidence: 99%
“…A presumptive diag-nosis is based on the presence of a typical lesion and either a reactive nontreponemal test and no history of syphilis or (for persons with a history of syphilis) a fourfold increase in titer on a quantitative nontreponemal test when results of past tests are compared with the most recent test results. In primary syphilis, the MHA-TP is less sensitive than the FTA-ABS test, and probably is less sensitive than the nontreponemal tests, when used to confirm reactivity in the nontreponemal test (87,111,114). A suggestive diagnosis of primary disease is based on the presence of a lesion and sexual contact within the preceding 90 days with a person in whom syphilis has been diagnosed.…”
Section: Sexually Acquired Syphilismentioning
confidence: 99%
“…As early as 1965, it was reported that 50 percent of positive reactions found using nontreponemal tests in a low‐risk population were false‐positive results 5 . False‐positive test results in the general population have been reported as 0.75 percent for the rapid plasma reagin (RPR) test, 0.96 percent for the microhemagglutination test, and 1.3 percent for the fluorescent treponemal antibody absorption (FTA‐ABS, Zeus Scientific, Raritan, NJ) test 10 . Studies to evaluate the false‐positive rate have been specifically conducted among individuals with diabetes 9 and rheumatoid arthritis 11 .…”
mentioning
confidence: 99%
“…5 False-positive test results in the general population have been reported as 0.75 percent for the rapid plasma reagin (RPR) test, 0.96 percent for the microhemagglutination test, and 1.3 percent for the fluorescent treponemal antibody absorption (FTA-ABS, Zeus Scientific, Raritan, NJ) test. 10 Studies to evaluate the false-positive rate have been specifically conducted among individuals with diabetes 9 and rheumatoid arthritis. 11 Ad-ditionally, cross-reacting treponemal antibodies associated with Lyme disease have been evaluated.…”
mentioning
confidence: 99%
“…After numerous studies and evaluations, a third-generation indirect immunofluorescence test, the fluorescent treponemal antibody absorption (FTA-ABS) procedure, has been acknowledged as the standard diagnostic technique with which other procedures are compared (5,7,12). Two hemagglutination procedures, the microhemagglutination T. pallidum test and the hemagglutination treponemal test for syphilis, have been recognized by the Centers for Disease Control as provisional techniques; these are also used in diagnostic laboratories (11,15,19).…”
mentioning
confidence: 99%